2019
DOI: 10.1002/etc.4512
|View full text |Cite
|
Sign up to set email alerts
|

Hitting Reset on Sediment Toxicity: Sediment Homogenization Alters the Toxicity of Metal‐Amended Sediments

Abstract: Laboratory testing of sediments frequently involves manipulation by amendment with contaminants and homogenization, which changes the physicochemical structure of sediments. These changes can influence the bioavailability of divalent metals, and field and mesocosm experiments have shown that laboratory‐derived thresholds are often overly conservative. We assessed the mechanisms that lead to divergence between laboratory‐ and field‐derived thresholds; specifically, we assessed the importance of slow equilibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…As noted earlier, this may be a result of development of more reducing condition within surface sediments (increasing Fe fluxes, SI Figure S3) and precipitation of metal sulfides that lowers porewater metal concentrations. 29,68 Possibly for similar reasons, sediment homogenization and short-term equilibration (lab-homogenized) further disturbed the established geochemical equilibrium within the sediments 27,57 and caused greater variability in the measured fluxes, resulting in increased uncertainty in the dose−response relationship (Figure 3c) and lower EC values with much wider confidence limits (SI Table S3). Therefore, using DGT TU measured in homogenized sediments to predict risks of toxicity was inferior compared with deployments in the field or equilibrated laboratory cores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted earlier, this may be a result of development of more reducing condition within surface sediments (increasing Fe fluxes, SI Figure S3) and precipitation of metal sulfides that lowers porewater metal concentrations. 29,68 Possibly for similar reasons, sediment homogenization and short-term equilibration (lab-homogenized) further disturbed the established geochemical equilibrium within the sediments 27,57 and caused greater variability in the measured fluxes, resulting in increased uncertainty in the dose−response relationship (Figure 3c) and lower EC values with much wider confidence limits (SI Table S3). Therefore, using DGT TU measured in homogenized sediments to predict risks of toxicity was inferior compared with deployments in the field or equilibrated laboratory cores.…”
Section: Resultsmentioning
confidence: 99%
“…However, the evidence linking higher DGT–metal fluxes to greater biological uptake and effects have been primarily drawn from studies in the laboratory under well controlled conditions, despite DGTs being highly amenable to in situ use. To enable the DGT technique as an effective line of evidence for assessing the risk of excessive bioavailable metal exposure and sediment toxicity, there is a major need to optimize its application in the field. It is well recognized that changes to metal bioavailability within sediments may occur during field sediment collection, and from homogenization or other disturbances before chemical or biological tests. ,, The overlying water conditions in the laboratory cannot be entirely matched to those existing in the field, resulting in significant differences in labile metal concentrations in overlying waters. …”
Section: Introductionmentioning
confidence: 99%
“…The need to improve the accuracy of ecological risk assessment, especially with regard to sediment manipulation before use in toxicity testing, was recently highlighted. 24 In the present study, the traditionally performed sediment manipulation was minimized because the use of intact whole sediment cores maintained natural layering and thereby contaminant availability in the sediments. As the upper centimeters of freshwater sediments are occupied by benthic organisms that live on top of and in the layered sediment, 1,57 a realistic exposure of the test species to sediment contamination was achieved in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…15 A variety of methods for the determination of bioavailable contaminant concentrations in sediment has been described; 14,1619 however, the manipulation of sediments (e.g., sieving and homogenization) that is required for application in toxicity tests and especially for bioavailability-based extractions leads to altered sediment characteristics, affecting layering and pore water concentrations of contaminants, 20 which can lead to over- or underestimation of sediment toxicity. 2124 Hence, the use of undisturbed sediments in laboratory toxicity testing mimics the natural situation most closely, increasing the realism of the sediment quality assessment. Similarly, the use of chronic life cycle bioassays mimics the exposure of organisms on relevant time scales, representing ecologically relevant endpoints, and should allow for a more realistic interpretation of sediment toxicity to benthic biota.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the main contributor of toxicity to C. dilutus was not the DDT but a degradation product dichlorodiphenyldichloroethane (DDD) that was produced over time. Costello, Harrison, Hammerschmidt, Mendonca, and Burton (2019) studied the impact of sediment manipulation such as homogenization on the results of toxicity bioassays using Hyalella azteca . They observed that toxicity thresholds that are artificially high may be produced when sediment is homogenized just before the toxicity assay is performed.…”
Section: Assessmentmentioning
confidence: 99%